Proper microsurgical nerve suture may impede Wallerian degeneration of completely transected nerves: an electron microscopic study - Eros Abrantes Erhart; Ciro Ferreira da Silva; Claudio Fava Chagas (Arquivos de Neuro-Psiquiatria)
Electron microscopic findings on the nerve of the biventer cervicis muscle of the chick, which was completely transected and immediately after submitted to an adequate microsurgical nerve suture, confirmed our previous statement that proper microsurgical nerve suture may impede the Wallerian degeneration that normally occurs in the distal segment of a completely transected nerve.